Could post-mortem computed tomography angiography inform cardiopulmonary resuscitation research?. (December 2017) - Rutty, Guy N.; Robinson, Claire; Amoroso, Jasmin; Coats, Tim; Morgan, Bruno
Abstract: Aim: Firstly, to develop an optimised chest compression post mortem computed tomography angiography protocol in the adult human during closed chest compression to investigate cardiopulmonary resuscitation blood flow, and secondly to provide preliminary observations of post-mortem anatomical cardiac chamber movement using a novel radiolucent static chest compression device. Methods: Variable volumes of radiological contrast agent were injected intravenously into a series of consented human cadavers. Each cadaver had chest compressions delivered with a LUCAS™2 mechanical chest compressor. Following each cycle of chest compressions, each cadaver was imaged with a Toshiba Aquilion CXL 128 slice computed tomography (CT) scanner to investigate the extent of contrast distribution. A chest compression simulator was then designed and built to allow static CT imaging of 1 cm incremental cadaver chest compressions to a depth of 5 cm. Results: Mechanical compressions: Ten cases were recruited for the CT angiography component of the study. Two were subsequently excluded from the study at the time of the initial, non-contrast PMCT scan. A further case was recruited in Emergency Department (ED). CT demonstrable antegrade arterial contrast distribution was achieved in 2 cases. The other 7 cases, including that undertaken in ED shortly after death, showed venous retrograde flow. Incremental compressions: Five new cases underwent incremental chest compression imaging. All cases demonstrated compression of the sternum, ribs, atria and great vessels. The right and left ventricles were not compressed, but moved laterally and inferiorly, further into the left chest cavity. The left hemi-diaphragm, stomach and liver moved inferiorly. The sternum, ventricles, hemi-diaphragm, stomach and liver all moved back to their original position on incremental release. Conclusion: The study suggests that with further protocol modification and access to human cadavers as near to death as possible, chest compression post mortem computed angiography (CCPMCTA) could be used as a model for the study of human vascular flow and heart movement during CPR.